Tracheobronchomegaly: a case series and review of the literature - Li, Zhenhua; Yang, Zhen; Niu, Yiran; Lei, Yan; Ni, Jixiang; Wang, Rujuan; Wen, Fangjing (Frontiers in Medicine, 2025)
BackgroundTracheobronchomegaly (TBM) is a rare condition characterized by abnormal dilation of the trachea and main bronchi owing to a pathological arrangement of smooth muscle fibers. Early identification and intervention are vital to halting progressive lung damage and improving the quality of life. This study aimed to examine the clinical characteristics, radiological features, and related complications in patients with TBM.Methods11 TBM cases were retrospectively identified through a review of chest computed tomography (CT) scans at our hospital between January 2018 and July 2025. We collected sputum or bronchoalveolar lavage fluid from 10 patients, and their clinical, radiological, and pulmonary function data were systematically collected and analyzed to assess disease characteristics and complications.ResultsAll 11 patients were male (mean age 79.2 ± 9.1 years). The main symptoms included recurrent infections, hemoptysis, productive cough, and dyspnea. The mean tracheal diameter was 32.4 [interquartile range (IQR):31.4–45.8]mm. Diverticula were present in four cases (36.4%, n = 4). Complications included bronchiectasis (45.5%, n = 5), chronic obstructive pulmonary disease (36.4%, n = 4), respiratory failure (9.1%, n = 1), tracheobronchopathia osteochondroplastica (9.1%, n = 1), and interstitial lung disease (9.1%, n = 1). Pulmonary function tests revealed obstructive (36.4%, n = 4), restrictive (27.3%, n = 3), and mixed (9.1%, n = 1) patterns. One patient died of respiratory failure.ConclusionIn this study, 11 cases involving a variety complications were analyzed in light of the current literature. TBM should be considered in patients who present with chronic cough, recurrent pulmonary infections, and bronchiectasis.